Sex-specific, high-sensitivity cardiac troponin T cut-off concentrations for ruling out acute myocardial infarction with a single measurement. Issue 1 (28th September 2018) - McRae, Andrew; Graham, Michelle; Abedin, Tasnima; Ji, Yunqi; Yang, Hong; Wang, Dongmei; Southern, Danielle; Andruchow, James; Lang, Eddy; Innes, Grant; Seiden-Long, Isolde; DeKoning, Lawrence; et al.
Abstract : CLINICIAN'S CAPSULE : What is known about the topic? Sex-specific, high-sensitivity cardiac troponin T (hs-cTnT) cut-offs increase the specificity of a myocardial infarction (MI) diagnosis. What did this study ask? Do sex-specific, hs-cTnT rule-out cut-offs enable ruling out MI in more patients while maintaining sensitivity? What did this study find? Sex-specific, hs-cTnT cut-offs ruled out MI in more patients than universal cut-offs; however, differences between sex-specific and universal cut-offs are small. Why does this study matter to clinicians? Sex-specific, rule-out, hs-cTnT cut-offs may enable more patients to be ruled out after a single hs-cTnT measurement. Abstract: Objective: Sex-specific diagnostic cut-offs may improve the test characteristics of high-sensitivity troponin assays for the diagnosis of myocardial infarction (MI). The objective of this study was to quantify test characteristics of sex-specific cut-offs of a single, high-sensitivity cardiac troponin T (hs-cTnT) assay for 7-day MI in patients with chest pain. Methods: This observational cohort study included consecutive emergency department (ED) patients with suspected cardiac chest pain from four Canadian EDs who had an hs-cTnT assay performed within 60 minutes of ED arrival. The primary outcome was MI at 7 days. We quantified test characteristics (sensitivity, negative predictive value [NPV], likelihood ratios and proportion of patients ruled out) for multiple combinations of sex-specific, rule-out cut-offs. We calculated the net reclassification index compared to universal rule-out cut-offs. Results: In 7, 130 patients (3, 931 men and 3, 199 women), the 7-day MI incidence was 7.38% among men and 3.78% among women. Optimal sex-specific cut-offs (<8 ng/L for men and <7 ng/L for women) had a 98.5% sensitivity for MI and ruled out MI in 55.8% of patients. This would enable an absolute increase in the proportion of patients who were able to be ruled out with a single hs-cTnT of 13.2% to 22.2%, depending on the universal rule-out concentration used as a comparator. Conclusions: Sex-specific hs-cTnT cut-offs for ruling out MI at ED arrival may improve classification performance, enabling more patients to be safely ruled out at ED arrival. However, differences between sex-specific and universal cut-off concentrations are within the variation of the assay, limiting the clinical utility of this approach. These findings should be confirmed in other data sets. Résumé: Objectif: L'établissement de valeurs-seuils diagnostiques selon le sexe pourrait améliorer les caractéristiques des dosages ultrasensibles de la troponine en vue du diagnostic d'infarctus du myocarde (IM). L'étude visait donc à quantifier les caractéristiques des valeurs-seuils selon le sexe d'un seul dosage ultrasensible de la troponine T cardiaque (TnTc) chez les patients souffrant de douleurs thoraciques, sur une période de 7 jours. Méthode: Il s'agit d'une étude observationnelle de cohorte, menée chez des patients consécutifs, examinés dans 4 services des urgences (SU), au Canada, pour des douleurs thoraciques évocatrices d'un IM et chez qui a été effectué un dosage de la TnTc dans les 60 minutes suivant leur arrivée à l'hôpital. Le principal critère d'évaluation consistait en la possibilité d'un IM au bout de 7 jours. Les caractéristiques de dosage (sensibilité, valeur prédictive négative, rapport de vraisemblance, proportion de patients éliminés) de différentes combinaisons de seuils d'élimination selon le sexe ont été quantifiées, et l'indice de reclassification net a été calculé par rapport aux seuils d'élimination généralement utilisés. Résultats: L'incidence de l'IM relevée au bout de 7 jours chez 7130 patients (3931 hommes et 3199 femmes) était de 7, 38 % chez les hommes et de 3, 78 % chez les femmes. Les seuils optimaux selon le sexe (hommes :<<8 ng/l; femmes :<7 ng/l) avaient une sensibilité de 98, 5 % à l'égard de l'IM et ils ont été utilisés pour éliminer la possibilité d'un IM chez 55, 8 % des patients. Leur application permettrait une augmentation absolue de la proportion de patients chez qui a été éliminée la possibilité d'un IM à l'aide d'un seul dosage de la TnTc, augmentation qui passerait de 13, 2 % à 22, 2 % selon les seuils d'élimination généralement reconnus, utilisés comme comparateur. Conclusions: L'application des seuils d'élimination d'un IM selon le sexe, à l'aide de la mesure de la TnTc à l'arrivée des malades au SU, pourrait améliorer la performance de classement du dosage, ce qui permettrait d'écarter, en toute sécurité, la possibilité d'un IM chez plus de patients qu'actuellement à leur arrivée au SU. Toutefois, comme les différences entre les seuils d'élimination selon le sexe et les seuils d'élimination généralement utilisés se situent dans la plage de variations du dosage, elles en limitent l'utilité clinique. Il faudrait que les résultats obtenus soient confirmés dans d'autres ensembles de données.